Dialectical Soundings and Politics in the Postnational Study of Music. (Revista Argentina de Musicología, 2010)
This article offers an overview of the nationalist ideas behind the development of musicology as a discipline, and focuses on the ways it articulated specific political projects in Latin America. The author suggests the notion of “dialectical soundings” as an alternate way to approach the study of sound and music that would allow for the questioning, critique, and moving beyond the nationalist-political projects that have defined musicological research.
Keywords: dialectical soundings; postnational; performance; Walter Benjamin; Latin America